PERBANDINGAN KUALITAS SPERMATOZOA SAPI JANTAN PASCA THAWING DENGAN PENGENCER YANG BERBEDA - Abdul Malik (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
The aim of this study was to evaluate the effects different extenders on motility, membrane and acrosome integrity of post-thawed bull sperm. Twenty ejaculates from four crossbreed bulls were collected. Within 5 min after sperm collection the fresh semen was divided into three groups based on types of extenders; (1) with Tris buffers, (2) with sodium citrate, and (3) with TALP extenders. A computer assisted semen analysis, hypo-osmotic swelling test, and fluorescence isothiocyanate labelled peanut agglutinin (FITC-PNA) techniques were used to determine motility, membrane integrity and acrosome integrity of spermatozoa, respectively, in both fresh ejaculate and frozen thawed semen. The percentage motility, membrane integrity and acrosome integrity in fresh ejaculate were higher than post-thawed. The sperm motility and membrane integrity were no significantly different (P> 0,05) among all extenders. Whereas, the membrane acrosome integrity of spermatozoa in post-thawed was significantly different (P< 0.05) when TALP extender was compared with sodium citrate, and Tris buffer extenders. In conclusion, all extenders resulted in a better sperm motility, membrane integrity after, while acrosome integrity was no significant after cryopreservation.